2021
DOI: 10.18203/2394-6040.ijcmph20214604
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of hemodialysis patients attending a tertiary care hospital in Delhi, India

Abstract: Background: CKD (chronic kidney disease) is one of the major complications of diabetes and hypertension. With increase in prevalence of non-communicable diseases, the patients presenting with the symptoms of CKD are also rising. Most of the patients suffering from CKD eventually land up on renal replacement therapy, putting extra burden economically as well as psychologically to the self and their family. The aim of the study is to find out the socio demographic and clinical profile of the patients suffering f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…7,8 However it was 2:1 in another similar study from India. 9 This was much higher than our study. Male predominance in various studies may be due to the paterchiarchial society and health seeking behavior of males are greater than females.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…7,8 However it was 2:1 in another similar study from India. 9 This was much higher than our study. Male predominance in various studies may be due to the paterchiarchial society and health seeking behavior of males are greater than females.…”
Section: Discussioncontrasting
confidence: 64%
“…This finding was similar to the study from Nepal and India. 9,11,12 However numerous studies from Nepal and abroad noted diabetes as the leading cause for CKD. 6,8,10 In another study, it was found that diabetic nephropathy (32.0%), hypertensive nephropathy (20.0%) and chronic glomerulonephritis (10.0%) to be the most common etiology of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…5 It is similar with the study from India and cameroon. 6,7 Mean age was 45.75 and most of the patients were in between 30 to 60 age group. This finding was similar to various studies from Nepal, India and cameroon.…”
Section: Discussionmentioning
confidence: 99%